Synergetic Effect of Bimetallic Au-Ru/TiO2 Catalysts for CO and Methanol Complete Oxidation - Calzada, L. (2019)
It is well known that gold nanoparticles supported on metal oxides are active in various reactions of environmental importance.1 Particularly, supported Au nanoparticles is well known as very efficient catalysts for CO oxidation at low temperature.1 It is also possible to perform the oxidation of some volatile organic compounds (VOCs) such as light hydrocarbons and alcohols at room temperature. The most efficient and low-cost method for their abatement is the catalytic combustion to CO2 and H2O, preferentially at low temperatures. On the other hand, the preparation of bimetallic catalysts has been proposed as an alternative to improve the activity, stability and/or selectivity of gold catalysts. In this way, the addition of a second metal could modify the physicochemical and electronic properties of the first metal.2 Ruthenium-based catalysts have been studied in VOCs oxidation reaction, and in conjunction with gold, they exhibit an improvement in catalytic activity.